Modern technologies and equipment for blowing extrusion of the films. Part 2, Trends in development of processing lines for one-stage blowing extrusion of the films - Stasiek, J. (Polimery, 2022)
In the review the directions in the development of construction of basic equipment of processing lines for one-stage blowing extrusion of the films, namely extruders, die heads, cooling systems (including the rings) and collecting units, were characterized. Special attention has been paid to rotary solutions of such equipment. Automation of the lines, especially those controlling the film thickness and related to it coordination of work of many elements of processing line, were discussed. Additionally, the use of simplified equations of energy balance for preliminary calculation of cooling path of multilayer film in the extrusion line has been presented with use of empirically determined average value of surface film conductance.